2014
DOI: 10.1371/journal.pone.0098145
|View full text |Cite
|
Sign up to set email alerts
|

Diapause Induction and Termination in Hyphantria cunea (Drury) (Lepidoptera: Arctiinae)

Abstract: The fall webworm, Hyphantria cunea (Drury), enters facultative diapause as a pupa in response to short-day conditions during autumn. Photoperiodic response curves showed that the critical day length for diapause induction was 14 h 30 min, 14 h 25 min and 13 h 30 min at 22, 25 and 28°C, respectively. The photoperiodic responses under non-24 h light–dark cycles demonstrated that night length played an essential role in the determination of diapause. Experiments using a short day length interrupted by a 1-h light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…1), with FWW only being found at relatively low elevations (up to 589 m in Xinglong County [117.5°E, 40.42°N]). FWW might now be expected to expand further in a southerly direction until other ranges such as the Qinling Mountains and Dabie Mountains are reached (Li et al, 2009;Chen et al, 2014) and this could lead to future admixture of the two groups. The northward expansion of the eastern group might be limited by low temperature to the north of the original introduction site in the early stages, while the recent expansions may reflect climate change in recent years (Yu & Li, 2015;Hu et al, 2016) or an evolutionary increase in cold hardiness in the cold region (Xu et al, 2015).…”
Section: Expansion Patternsmentioning
confidence: 99%
“…1), with FWW only being found at relatively low elevations (up to 589 m in Xinglong County [117.5°E, 40.42°N]). FWW might now be expected to expand further in a southerly direction until other ranges such as the Qinling Mountains and Dabie Mountains are reached (Li et al, 2009;Chen et al, 2014) and this could lead to future admixture of the two groups. The northward expansion of the eastern group might be limited by low temperature to the north of the original introduction site in the early stages, while the recent expansions may reflect climate change in recent years (Yu & Li, 2015;Hu et al, 2016) or an evolutionary increase in cold hardiness in the cold region (Xu et al, 2015).…”
Section: Expansion Patternsmentioning
confidence: 99%
“…Throughout the pre-experimental rearing stages, caterpillars were reared at a density of 20-30 individuals per dish in an environmental chamber set at 25°C and L16:D8 photoperiod. This photoperiodic condition was chosen to prevent caterpillars from entering diapause regardless of the experimental temperature they were exposed to (Gomi, 1997;Takeda, 2005;Chen et al, 2014).…”
Section: Study Insectmentioning
confidence: 99%
“…Until recently, several studies have investigated biological aspects of H. cunea, including life-history and voltinism (Gomi & Takeda, 1996;Gomi, 2007;Gomi et al, 2007Gomi et al, , 2009), host-plant preferences and performance (Morris, 1967;Greenblatt et al, 1978;Williams & Myers, 1984), and diapause (Gomi, 1997;Li et al, 2001;Chen et al, 2014). To the best of our knowledge, this is the first work that investigates how the thermal responses of this generalist caterpillar are altered by the nutritional quality of host plant.…”
Section: Introductionmentioning
confidence: 99%
“…The central importance of night length was also seen in data for the flesh fly Sarcophaga argyrostoma (Robineau-Desvoidy) 5 in which the incidence of pupal diapause was very low in cycles containing a short night (eg, LD 12:8 and LD 16:8) with non-24-h light-dark cycles in which photophases of 10, 12, 14, and 16 h were combined with different lengths of scotophase of 4-24 h have been carried out on the zygaenid moth Pseudopidorus fasciata (Felder & Felder, 1862), the pine caterpillars Dendrolimus punctatus (Walker), the rice stem borer Chilo suppressalis (Walker), the Asian corn borer Ostrinia furnacalis, and the fall webworm Hyphantria cunea in our laboratory. [6][7][8][9][10] The photoperiodic response curves in these species all showed that the incidence of larval diapause was low or zero in cycles containing a short night (4 and 8 h), but high in cycles containing a long night (12,16,20, and 24 h), regardless of the length of the photophase, indicating that the length of the scotophase plays an essential role in the determination of diapause in these species.…”
Section: Introductionmentioning
confidence: 90%